Meningkatkan Nilai Karakter Peserta Didik Melalui Penerapan Model Pembelajaran Project Based Learning - Setiono, Panut; Yuliantini, Nani; Dadi, Sri (Jurnal PGSD, 2020)
This study aims to determine the application of the Project-Based Learning model to improve student character values in integrative thematic learning lectures on Environmental Themes in PGSD FKIP study programs in Bengkulu University. This research is a class action research conducted in the Academic Year 2019/2020. Data collection techniques used were observation, interviews, and documentation. The results showed an increase in character values in aspects of friendly, critical, creative, curious, thorough, and care for the environment. Conclusions in this study, the project-based learning model can improve the character values of students.